Integrated photonic chip for quantum key distribution - Zhang, Gong (2019)
Silicon photonic technologies exploit silicon as an optical material to build a wide array of devices and systems. The flexibility, modularity, and stability of silicon photonic systems provide unprecedented opportunities for next-generation quantum key distribution (QKD) and quantum networking. This doctoral thesis focuses on the design, simulation, fabrication, and experiment of QKD chips based on silicon photonics. Crucial components for QKD chips are designed and fabricated, including the grating coupler, polarization beam splitter, polarization rotator, modulator, photodetector, ring resonator, and interferometer. Using these components, chip-based continuous variable quantum key distribution (CV-QKD) is demonstrated for the first time. The chip-based CV-QKD system is capable of producing a secret key rate of 9.3 kbits/s (under collective attack) at a distance of 100 km in fiber. The successful demonstration of a single chip-based QKD offers new possibilities for low-cost, scalable and portable quantum networks.